Casting Processes and Modelling of Metallic Materials - Abdallah, Zakaria; Aldoumani, Nada (IntechOpen, 2021)
This book, Casting Processes and Modelling of Metallic Materials, explores the various casting and modelling activities related to metallic alloy systems. The book provides results of research work conducted by experts from all over the globe to add to the research community in the era of the casting process and modelling. The book was edited by two experts in the field of materials science and modelling, Dr. Abdallah and Dr. Aldoumani, whom both have several publications in peer-reviewed journals, worldwide conferences, and scientific books. The book introduces the casting processes and then discusses the various issues and possible solutions. Over the past years, various models have been proposed and utilized to predict the performance of castings. Some of these models proved to be accurate whereas others failed to predict the casting performance. The strength of any predictive tool depends on the employment of physically meaningful parameters that replicate the real-life conditions. This has been illustrated in the current book with such predictive models and finite element (FE) modelling to illustrate the behaviour of castings in real-life conditions.